GAYA BAHASA PERSUASIF SELEBGRAM ACEH - Nurrahmah, Nurrahmah; Wirduna, Wirduna; Alfurqan, Alfurqan; Zulfadhli, Zulfadhli (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Persuasive language style is a style of language that is used with the aim of influencing the interlocutor. This style of language can be found in the speech of Acehnese celebrities when they endorse a product. This style of language is used to conjure up Instagram users or so-called followers to be interested in the goods and services offered by the celebgram. Even though they only rely on language style, in fact the celebrities are able to increase the turnover of online business people who use their services. This is because the language style used is unique, interesting, and creative. In addition, the language style is also combined with persuasive techniques owned by each celebrity. For this reason, this study aims to describe the style of persuasive language and persuasive techniques used by Acehnese celebrities as a strategy in endorsement. The data source of this research is the celebgram speech taken from the Aceh celebrity instagram story which consists of four accounts, namely 1) @cutbul-real, 2) @herlinkenza, 3) @devi.dean , 4) @kakaalfarisi, and 5) @khalidamakmoer . The five accounts were chosen because of the large number of followers and the five celebgrams are the most phenomenal celebs today. The data in this study are in the form of verbal and verbal data, namely the construction of sentences in the celebgram speech that shows a persuasive language style. The data collection was carried out in several stages, namely recording the speech of the Acehnese celebrity, recording the speech in the form of persuasive language, classifying the data, analyzing the data, and drawing conclusions. Furthermore, data analysis was carried out with steps of data reduction, data presentation, and drawing conclusions. The results show that the style of language used is in the form of affirmation, comparison, and satire. The persuasion technique used, rationalization technique, compensation technique, and suggestion